Multidisciplinary Management of Cavernous sinus thrombosis: Early Recognition, Rapid Response, and Integrated Hospital Care Pathways-An Updated Review - Aldossari, Mobarak Fahad Mobarak; Mohammed Mesfer Mohammed Aldawsari; Ahmad Talal Matar Almarshadi; Minahi Fehaid Musaibeeh Alotaibi; Ahmed Alsulayyih; Saber Hamed Maqbul Alsharari; Naji Mohammed Saleh Al-Qahtani; Hassan Mohammed Mohammed Tomihi; Fares Zaban Alrowiliy; Youssef Farhan H Alsharari; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Cavernous sinus thrombosis (CST) is a rare but life-threatening cerebrovascular disorder most often arising from septic spread of infections in the facial, sinus, orbital, or dental regions. Its rapid progression, involvement of critical neurovascular structures, and potential for severe neurological deficits necessitate prompt clinical recognition and multidisciplinary management. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide an updated, integrated overview of CST, focusing on early recognition, diagnostic approaches, and comprehensive inpatient management strategies to improve clinical outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review methodology was used, synthesizing current evidence on CST etiology, epidemiology, pathophysiology, clinical presentation, diagnostic imaging, and therapeutic interventions. Sources include retrospective studies, expert consensus, and observational data due to the absence of randomized clinical trials. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CST predominantly originates from infections in the nasolabial triangle, paranasal sinuses, or orbit, with Staphylococcus aureus representing the most common pathogen. Clinical manifestations include fever, severe headache, periorbital edema, ophthalmoplegia, and cranial nerve dysfunction. Contrast-enhanced CT or MR venography is essential for diagnosis. Management centers on aggressive broad-spectrum antimicrobial therapy and anticoagulation, with surgical intervention reserved for drainage of primary infectious sources. Contemporary treatment has significantly reduced mortality to approximately 8–13%, although long-term sequelae such as visual impairment and persistent cranial nerve deficits remain common. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early diagnosis combined with prompt antimicrobial therapy, carefully selected anticoagulation, and multidisciplinary care is essential for improving CST outcomes. Continued clinical vigilance and standardized management pathways are critical to minimizing morbidity.